Nutritional composition and antioxidant capacity of Urtica hyperborea: A phytofood of Trans-Himalayan region of Ladakh, India - Zomba, Disket; Dar, Mushtaq Ahmad; Jandrotia, Rupali; Sharma, Mansi; Singh, Rishikesh; Kaur, Shalinder; Batish, Daizy R. (Journal of Phytology, 2023)
Urtica hyperborea Jacquem. ex Wedd., a perennial plant of Urticaceae family is considered as a wild vegetable in the mountainous region of Ladakh. Due to its application in many forms of traditional culinary in every household during the harsh winter season, the plant ensures the food security. However, the nutritional composition and phytochemical analysis of U. hyperborea responsible for these beneficial features have not been explored widely. The present study aims to determine the nutritional composition (e.g., macromolecules, pigments, minerals, phenolics and flavonoid contents), antioxidant activity and the phytochemical analysis of this plant species present in Ladakh, India. The radical scavenging and antioxidant potential of the plant were evaluated by assays like 2,2‒diphenyl‒1‒picrylhydrazyl (DPPH), hydrogen peroxide (H2O2), hydroxyl (ºOH), and ferric ion reducing antioxidant power (FRAP) for different extracts prepared in water, methanol, ethyl acetate, and petroleum ether. Macromolecules such as protein, carbohydrate, total phenolic and flavonoid contents in U. hyperborea were found to be 62.28±6.67, 170.80±3.98, 24.47±0.39 and 5.43±0.97 mg g-1, respectively. Similarly, dried powder of U. hyperborea was found to be rich in different mineral contents such as potassium, magnesium, sodium, manganese, zinc and iron. Among the various solvents used for exploring scavenging and antioxidant potential, aqueous extracts showed highest activity with 79.2% in DPPH assay as compared to other extracts. Similar trend was observed for other assays where aqueous extracts exhibited higher activity followed by methanolic, ethyl acetate and petroleum ether extracts. Significant positive linear correlations were observed between the radical scavenging/antioxidant activity of aqueous extracts and their content of phenolic/flavonoid compounds. The identification of phenolic compounds such as coumarin, quercetin, and ferulic acid confirm the antioxidative nature of the plant. Overall, rich macromolecule and mineral contents, as well as higher radical scavenging/antioxidant activities in aqueous extracts of U. hyperborea revealed that the plant has significant potential to be utilized as a phytofood source in harsh environmental conditions.